Insight into gut dysbiosis of patients with inflammatory bowel disease and ischemic colitis - Dahal, Ram Hari; Kim, Shukho; Kim, Yu Kyung; Kim, Eun Soo; Kim, Jungmin (Frontiers in Microbiology, 2023)
The collection of whole microbial communities (bacteria, archaea, fungi, and viruses) together constitutes the gut microbiome. Diet, age, stress, host genetics, and diseases cause increases or decreases in the relative abundance and diversity of bacterial species (dysbiosis). We aimed to investigate the gut microbial composition at different taxonomic levels of healthy controls (HCs) with active Crohn’s disease (CD), ulcerative colitis (UC), and ischemic colitis (IC) using culture- and non-culture-based approaches and identify biomarkers to discriminate CD, UC, or IC. We determined the specific changes in the gut microbial profile using culture-independent (16S rRNA gene amplicon sequencing) as well as culture-based (culturomic) approaches. Biomarkers were validated using quantitative Real-Time PCR (qPCR). In both methods, bacterial diversity and species richness decreased in disease-associated conditions compared with that in HCs. Highly reduced abundance of Faecalibacterium prausnitzii and Prevotella sp. and an increased abundance of potentially pathogenic bacteria such as Enterococcus faecium, Enterococcus faecalis, and Escherichia coli in all CD, UC, or IC conditions were observed. We noted a high abundance of Latilactobacillus sakei in CD patients; Ligilactobacillus ruminis in UC patients; and Enterococcus faecium, Escherichia coli, and Enterococcus faecalis in IC patients. Highly reduced abundance Faecalibacterium prausnitzii and increased abundance of Latilactobacillus sakei and Enterococcus faecium in CD, Ligilactobacillus ruminis and Enterococcus faecium in UC, and Enterococcus faecium, Escherichia coli, and Enterococcus faecalis in IC could be biomarkers for CD, UC, and IC, respectively. These biomarkers may help in IBD (CD or UC) and IC diagnosis.